2020
DOI: 10.1111/jcmm.16093
|View full text |Cite
|
Sign up to set email alerts
|

CircSAMD4A aggravates H/R‐induced cardiomyocyte apoptosis and inflammatory response by sponging miR‐138‐5p

Abstract: Hypoxia/reoxygenation (H/R)‐induced myocardial cell injury is the main cause of acute myocardial infarction (AMI). Many proofs show that circular RNA plays an important role in the development of AMI. The purpose of this study was to investigate the role of circSAMD4A in H/R‐induced myocardial injury. The levels of circular SAMD4A (circSAMD4A) were detected in the heart tissues of AMI mice and H/R‐induced H9C2 cells, and the circSAMD4A was suppressed in AMI mice and H/R‐induced H9C2 cells to investigate its’ f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…Evidence-Based Complementary and Alternative Medicine et al showed that miR-138-5p was downregulated in H9C2 cells after H/R treatment and miR-138-5p can promote H/Rinduced cardiomyocyte apoptosis and inflammation in vitro [19]. miR-16-5p is a miRNA located on human chromosome 3, which plays an important role in the process of cardiomyocyte apoptosis and cardiovascular formation [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence-Based Complementary and Alternative Medicine et al showed that miR-138-5p was downregulated in H9C2 cells after H/R treatment and miR-138-5p can promote H/Rinduced cardiomyocyte apoptosis and inflammation in vitro [19]. miR-16-5p is a miRNA located on human chromosome 3, which plays an important role in the process of cardiomyocyte apoptosis and cardiovascular formation [13].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al showed that inhibiting miR-101-3 p can inhibit the activation of the JAK2/STAT3 signaling pathway and downregulate the apoptosis of cardiomyocytes after H/R treatment [ 18 ]. And Hu et al showed that miR-138-5 p was downregulated in H9C2 cells after H/R treatment and miR-138-5 p can promote H/R-induced cardiomyocyte apoptosis and inflammation in vitro [ 19 ]. miR-16-5p is a miRNA located on human chromosome 3, which plays an important role in the process of cardiomyocyte apoptosis and cardiovascular formation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, circRNA ITCH mediates H 2 O 2 -induced myocardial cell apoptosis by upregulating miR-17-5p via wnt/β-catenin signaling pathway (115). circSAMD4A aggravates hypoxia/reoxygenation (H/R)-induced cardiomyocyte apoptosis and inflammatory response by sponging miR-138-5p (116).…”
Section: Circrna and Cvdsmentioning
confidence: 99%
“…22 MiR-138-5p, as a member of miRNAs, is closely associated with various human diseases, including several types of cancers, [23][24][25] obesity, 26 and especially for inflammatory diseases. 27,28 Of inflammatory illnesses, miR-138-5p has been found downregulated in acute myocardial infarction model induced by hypoxia/reoxygenation 27 and chondrocytes of osteoarthritis model caused by IL-1β. 28 Conversely, miR-138-5p was overexpressed in pulmonary arterial smooth muscle cells/ lungs in patients or rats of pulmonary arterial hypertension, which could be alleviated by inhibiting the miR-138-5p expression.…”
Section: Introductionmentioning
confidence: 99%
“…10,14,[44][45][46] Accumulating evidence indicated the vital role of miR-138-5p in the development and homeostasis of the immune system. [23][24][25][26][27][28] In the majority, miR-138-5p seems to act as a tumor-suppressor miRNA by targeting specific oncogenic genes and is also being deregulated in cancer cells, such as glioma, 23 non-small cell lung cancer, 24 ovarian 47 and prostate cancer. 25 In the present study, low expression of miR-138-5p was found in the rat hippocampus of the cognitive impairment model and RM microglial cells stimulated with LPS.…”
mentioning
confidence: 99%